2015
DOI: 10.3389/fnbeh.2015.00125
|View full text |Cite
|
Sign up to set email alerts
|

Beta-adrenergic receptors support attention to extinction learning that occurs in the absence, but not the presence, of a context change

Abstract: The noradrenergic (NA)-system is an important regulator of cognitive function. It contributes to extinction learning (EL), and in disorders where EL is impaired NA-dysfunction has been postulated. We explored whether NA acting on beta-adrenergic-receptors (β-AR), regulates EL that depends on context, but is not fear-associated. We assessed behavior in an “AAA” or “ABA” paradigm: rats were trained for 3 days in a T-maze (context-A) to learn that a reward is consistently found in the goal arm, despite low reward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

6
1

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 83 publications
3
18
0
Order By: Relevance
“…Experiments were conducted in a T-maze that was composed of a starting box (25 × 20 cm) that was separated from the main corridor (100 × 20 cm) by a sliding door and two side corridors (40 × 10 cm) positioned perpendicular to the other end of the main corridor. The maze design and the protocol followed was as described previously (Wiescholleck et al, 2014 ; André et al, 2015a , b ). The context of the maze was changed by exchanging the plastic floor of the maze (zebra stripes, checkered patterns, or geometric lines), odor cues that were placed at the end of the goal arms, and exchanging the extra-maze cue cards that were placed 40 cm above the end of the main corridor (Wiescholleck et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Experiments were conducted in a T-maze that was composed of a starting box (25 × 20 cm) that was separated from the main corridor (100 × 20 cm) by a sliding door and two side corridors (40 × 10 cm) positioned perpendicular to the other end of the main corridor. The maze design and the protocol followed was as described previously (Wiescholleck et al, 2014 ; André et al, 2015a , b ). The context of the maze was changed by exchanging the plastic floor of the maze (zebra stripes, checkered patterns, or geometric lines), odor cues that were placed at the end of the goal arms, and exchanging the extra-maze cue cards that were placed 40 cm above the end of the main corridor (Wiescholleck et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…Every day, rats engaged in a learning session that comprised 20 consecutive trials, that were split into two data blocks (1st ten, 2nd ten trials), for analysis purposes (see below, and Wiescholleck et al, 2014 ; André et al, 2015a , b ). The trial commenced when the door to the starting box was opened and the animal entered the maze.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In consequence, it is conceivable that the renewal effect is dependent on attentional and encoding processes that occur during extinction learning and thus may be mediated by neurotransmitter systems involved in learning and attention, such as the noradrenergic and dopaminergic systems (Lauzon et al, 2009 ). Recent studies in humans and rats meanwhile showed that while stimulation of the noradrenergic system actually enhanced extinction learning, it had no impact upon the strength of the renewal effect (André et al, 2015 ; Lissek et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%